2009
DOI: 10.1007/s00415-009-5222-3
|View full text |Cite
|
Sign up to set email alerts
|

No increase in adverse pregnancy outcomes for women receiving antiepileptic drugs

Abstract: The objectives of this study were (1) to investigate the incidence of adverse pregnancy outcomes among the epileptic and general populations, including small for gestational age (SGA), low birth weight (LBW) and preterm delivery, using two large-scale nationwide population-based databases, and (2) to compare the risk of these adverse pregnancy outcomes between epileptic women who did and who did not receive antiepileptic drug (AED) treatment during pregnancy. This study used two national datasets: the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
1
16
2
5
Order By: Relevance
“…On the other hand, recent studies have suggested an increased risk of premature delivery limited to WWE using AED . Nonetheless, there are contradictory results suggesting a higher risk of premature delivery only for WWE without AED .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent studies have suggested an increased risk of premature delivery limited to WWE using AED . Nonetheless, there are contradictory results suggesting a higher risk of premature delivery only for WWE without AED .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 2830 women, 703 (24.8%) were prescribed PTU or MMI treatment during pregnancy. Because there is no documented clinical consensus on a defined dosage or time period that qualifies a patient as being ‘on’ or ‘off’ the medication, we defined receiving antithyroid treatment as women prescribed an antithyroid drug for more than 30 days during pregnancy 30 …”
Section: Methodsmentioning
confidence: 99%
“…Because there is no documented clinical consensus on a defined dosage or time period that qualifies a patient as being 'on' or 'off' the medication, we defined receiving antithyroid treatment as women prescribed an antithyroid drug for more than 30 days during pregnancy. 30 We selected the comparison group from the remaining 208 433 women in the database. We excluded women with a diagnosis of hyperthyroidism anytime during the period 1996-2006 (because Taiwan implemented National Health Insurance in 1995, there are no medical data before 1996).…”
Section: Study Samplementioning
confidence: 99%
“…In order to increase the validity of epilepsy diagnoses, we only included epilepsy cases if they had at least three consensus diagnoses of epilepsy within 5 years prior to their index date. This criterion has been used in prior studies [16]. In addition, these epilepsy patients had all been prescribed with antiepileptic medication.…”
Section: Exposure Assessmentmentioning
confidence: 99%